Heteroleptic copper(I) photosensitizers of dibenzo[b, j]-1, 10-phenanthroline derivatives driven hydrogen generation from water reduction. (November 2016) - Luo, Shu-Ping; Chen, Nan-Yu; Sun, Yuan-Yuan; Xia, Liang-Min; Wu, Zhi-Cai; Junge, Henrik; Beller, Matthias; Wu, Qing-An
Abstract: A series of dibenzo[b, j]-1, 10-phenanthroline derivatives as N ligands was synthesized and their heteroleptic copper complexes obtained in-situ. These were applied as photosensitizer in photocatalyticCu-Fe water reduction system. Thixantphos as P ligand and 5, 8-diphenyl-6, 7-dihydrodibenzo[b, j] [1, 10]phenanthroline as N ligands constitutes the most efficient photosensitizer among the tested photosensitizer. The highest turnover number of copper was up to 441 and the system achieved a stability of 15 h. Photophysical and electronic chemical character showed that the longer exited time of Cu complex is the reason for the higher photosensitive activity. By theoretical calculation it could be proven that ligand-to-ligand charge transfer is the main energy transition method. Noteworthy, for the first time it could be detected and explained why a C-C single bond at 6, 7 positions of phenanthroline could significantly increase the light conversion efficiency. This is a result of the lower N ligand contribution in HOMO and the wider energy gap. Graphical abstract: A series of dibenzo[b, j]-1, 10-phenanthroline derivatives as N ligands was synthesized and their heteroleptic copper complexes were applied as photosensitizer in photocatalytic Cu-Fe water reduction system. The highest turnover number of copper was up to 441 and the system achieved a stability of 15 h. Noteworthy, for the first time it could be detected and explained why a C-C single bond at 6, 7 positions of phenanthroline could significantly increase the light conversion efficiency. Highlights: A series of dibenzo[b, j]-1, 10-phenanthroline derivatives as N ligands have been synthesized. The structure–activity relationships of their heteroleptic copper complexes have been discussed. C-C single bond at 6, 7 positions of phenanthroline could significantly increase the light conversion efficiency.